1991
DOI: 10.1002/1097-0142(19910315)67:6<1661::aid-cncr2820670630>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of ABH(O) blood group antigen expression in intraepithelial dysplastic lesions to clinicopathologic properties of associated transitional cell carcinoma of the bladder

Abstract: Paraffin-embedded, giant-step sections of 13 bladders with transitional cell carcinomas were stained with monoclonal anti-A or anti-B antibodies to investigate whether intraepithelial dysplastic lesions are related to obvious tumors. Normal and/or hyperplastic lesions were retained in only eight bladders; severe dysplasia and/or carcinoma in situ were found in all bladders except two. AB-antigen expression was retained in intraepithelial lesions of bladders with invasive carcinoma. Most intraepithelial lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…A reduction in blood-group A antigen (GalNAca1-3[Fuca1-2]Galb1-3GlcNAc-R) expression was reported in transitional cell carcinoma (TCC) of the bladder and showed significant correlation with an invasive phenotype. [8][9][10][11] Orntoft and Wolf 12 examined the correlation between blood-group antigen expression and the activity of glycosyltransferases in TCC of the bladder and reported that the activity of A glycosyl transferase was severely reduced in tumors showing loss of A antigen expression. This phenomenon drew our attention, due to the fact that the determinant of the ABO blood-group antigen is synthesized by the action of the ABO gene encoding ABO glycosyltransferase assigned to chromosome 9q34.1, where loss of heterozygosity (LOH) was frequently reported in bladder cancer.…”
mentioning
confidence: 99%
“…A reduction in blood-group A antigen (GalNAca1-3[Fuca1-2]Galb1-3GlcNAc-R) expression was reported in transitional cell carcinoma (TCC) of the bladder and showed significant correlation with an invasive phenotype. [8][9][10][11] Orntoft and Wolf 12 examined the correlation between blood-group antigen expression and the activity of glycosyltransferases in TCC of the bladder and reported that the activity of A glycosyl transferase was severely reduced in tumors showing loss of A antigen expression. This phenomenon drew our attention, due to the fact that the determinant of the ABO blood-group antigen is synthesized by the action of the ABO gene encoding ABO glycosyltransferase assigned to chromosome 9q34.1, where loss of heterozygosity (LOH) was frequently reported in bladder cancer.…”
mentioning
confidence: 99%
“…Studies have found that large proportion of transitional epithelia of bladder carcinoma had either reduced expression of blood type antigen A or loss of A allele [ 31 , 32 ]. A reduction in the expression of antigen A was correlated with the invasiveness of the malignancies [ 33 ]. These pathological findings suggest that the determinants of ABO blood type antigens may play a critical role in the development of urinary bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phenotypic biochemical markers, such as G-actin and M344 antigen, occur as early events in uroepithelial transformation (44,102,103). Blood group antigen alterations have been identified even in dysplasias of the urothelium (104,105). Similarly, unscheduled expression of cytokeratin 20 has been reported as a marker of urothelial dysplasia (106).…”
Section: Bladder Cancer As a Model For The Study Of Preneoplastic Lesmentioning
confidence: 91%